2008
DOI: 10.1128/jb.00455-08
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation ofswrAAand Motility inBacillus subtilis

Abstract: We demonstrate that transcription of the gene swrAA, required for swarming migration in Bacillus subtilis, is driven by two promoters: a sigD-dependent promoter and a putative sigA-dependent promoter, which is inactive during growth in liquid Luria-Bertani medium and becomes active in the presence of the phosphorylated form of the response regulator DegU or on semisolid surfaces. Since sigD transcription is enhanced by SwrAA, this finding reveals that swrA expression is controlled by a positive feedback loop. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 34 publications
3
62
0
Order By: Relevance
“…The swrAA 2 motility phenotype could be suppressed by a fla/che promoter upmutation, and microarray experiments indicated that SwrAA enhances expression of the fla/che operon, acting on the s A -dependent promoter P fla/che(A) (Kearns & Losick, 2005). Several lines of evidence point to a cooperation between SwrAA and DegU~P in motility (Kobayashi, 2007;Verhamme et al, 2007;Calvio et al, 2008) and here we demonstrate not only that the two proteins must cooperate to drive c-PGA production, but also that such an effect is achieved independently of the activation of the fla/che promoter.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The swrAA 2 motility phenotype could be suppressed by a fla/che promoter upmutation, and microarray experiments indicated that SwrAA enhances expression of the fla/che operon, acting on the s A -dependent promoter P fla/che(A) (Kearns & Losick, 2005). Several lines of evidence point to a cooperation between SwrAA and DegU~P in motility (Kobayashi, 2007;Verhamme et al, 2007;Calvio et al, 2008) and here we demonstrate not only that the two proteins must cooperate to drive c-PGA production, but also that such an effect is achieved independently of the activation of the fla/che promoter.…”
Section: Introductionmentioning
confidence: 99%
“…Swimming and swarming assays were performed as already described (Calvio et al, 2008). Motility was scored as positive when cells colonized the entire 8.5 cm plate in 13 h at 30 uC.…”
Section: Strainmentioning
confidence: 99%
See 3 more Smart Citations